2011
DOI: 10.14742/ajet.925
|View full text |Cite
|
Sign up to set email alerts
|

Self reflection and preservice teachers' technological pedagogical knowledge: Promoting earlier adoption of student-centred pedagogies

Abstract: <span>The purpose of this paper is to present the qualitative findings relating to fourteen preservice teachers' development and translation of their technological pedagogical knowledge (TPK) into their classroom practices throughout the first year of their teacher preparation program. It was found that all fourteen participants demonstrated a gain in both technological and pedagogical knowledge, and registered positive changes both in their pedagogical beliefs and their beliefs in using information and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
2
19
0
1
Order By: Relevance
“…Another finding was the importance of learning instructional design, instructional analyses, and instructional technologies and how to use them in their teaching in order to improve students' ITOE. Similar findings have been evident in interventional studies (Agyei & Voogt, 2012;Angeli & Valanides, 2009;Gao et al, 2011). Agyei and Voogt (2012) reported that interventions designed to improve technology and TPACK are effective, and pre-service teachers have begun to think about technology usage in their work.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Another finding was the importance of learning instructional design, instructional analyses, and instructional technologies and how to use them in their teaching in order to improve students' ITOE. Similar findings have been evident in interventional studies (Agyei & Voogt, 2012;Angeli & Valanides, 2009;Gao et al, 2011). Agyei and Voogt (2012) reported that interventions designed to improve technology and TPACK are effective, and pre-service teachers have begun to think about technology usage in their work.…”
Section: Discussionsupporting
confidence: 73%
“…In parallel with TPACK literature, research on pre-service teachers' technology integration knowledge and abilities has been limited Pamuk, 2012;Papastergiou, 2010;Semiz & Ince, 2012). In addition, a limited number of studies have examined the effects of technology intervention on pre-service and in-service PE teachers' technology integration and TPACK variables (Agyei & Voogt, 2012;Angeli & Valanides, 2009;Gao, Tan, Wang, Wong, & Choy, 2011;Kramarski & Michalsky, 2010;Mccaughtry, Oliver, Dillon, & Martin, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Agyei and Voogt (2012) and Gao et al (2011) indicated that interventions designed to develop technology integration by pre-service teachers were effective, and as a result of interventions, pre-service teachers began to consider technology as a tool for developing student learning, instead of simply viewing technology as a tool for reinforcement or demonstration.…”
Section: Tpack Studiesmentioning
confidence: 99%
“…If the learning environment for technology integration competency is well established, both pre-service and in-service teachers can improve their TPACK scores (Angeli & Valanides, 2009;Agyei & Voogt, 2012, Gao et al, 2011.…”
Section: Tpack Studiesmentioning
confidence: 99%
“…Collaborative learning is emphasised in research focusing on one-to-one computing (Chan et al 2006): even though each student has his or her own mobile ICT tools, these tools can be used for fostering collaboration with peers. Gao et al (2011) found a positive connection between pre-service teachers' development of TPK and their ability to engage with student-centered pedagogies.…”
Section: Technological Pedagogical Knowledgementioning
confidence: 86%